2020
DOI: 10.3390/antiox9060555
|View full text |Cite
|
Sign up to set email alerts
|

The Hypoxia Tolerance of the Goldfish (Carassius auratus) Heart: The NOS/NO System and Beyond

Abstract: The extraordinary capacity of the goldfish (Carassius auratus) to increase its cardiac performance under acute hypoxia is crucial in ensuring adequate oxygen supply to tissues and organs. However, the underlying physiological mechanisms are not yet completely elucidated. By employing an ex vivo working heart preparation, we observed that the time-dependent enhancement of contractility, distinctive of the hypoxic goldfish heart, is abolished by the Nitric Oxide Synthase (NOS) antagonist L-NMMA, the Nitric Oxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 89 publications
(131 reference statements)
1
16
0
Order By: Relevance
“…This increases myocardial efficiency (i.e., the force generated per O 2 consumed), thus contributing to maintain myocardial function (Stecyk et al 2004). In line with these observations, studies from our lab revealed in the isolated goldfish heart that acute hypoxia (~ 1.5 mg O 2 L −1 ) is accompanied by an increased myocardial NOS expression (Imbrogno et al 2014), and that the NOS-derived NO is crucial for the hypoxia-dependent increase of myocardial contractility, typical of this teleost (Filice et al 2020b). This is supported by the hypoxiainduced activation of the phosphatidylinositol-3 kinase (PI3-K)/protein kinase B (Akt) pathway, a well-known player in the NOS-dependent NO production (Carrillo-Sepulveda et al 2010), and SERCA2a pumps modulation, whose inhibition under hypoxia significantly reduced the timecourse increase of the goldfish heart performance (Filice et al 2020b).…”
Section: Hypoxiasupporting
confidence: 72%
“…This increases myocardial efficiency (i.e., the force generated per O 2 consumed), thus contributing to maintain myocardial function (Stecyk et al 2004). In line with these observations, studies from our lab revealed in the isolated goldfish heart that acute hypoxia (~ 1.5 mg O 2 L −1 ) is accompanied by an increased myocardial NOS expression (Imbrogno et al 2014), and that the NOS-derived NO is crucial for the hypoxia-dependent increase of myocardial contractility, typical of this teleost (Filice et al 2020b). This is supported by the hypoxiainduced activation of the phosphatidylinositol-3 kinase (PI3-K)/protein kinase B (Akt) pathway, a well-known player in the NOS-dependent NO production (Carrillo-Sepulveda et al 2010), and SERCA2a pumps modulation, whose inhibition under hypoxia significantly reduced the timecourse increase of the goldfish heart performance (Filice et al 2020b).…”
Section: Hypoxiasupporting
confidence: 72%
“…The same occurs in hypoxia-tolerant fish in which, as observed in the perfused goldfish heart, exposure to low O 2 is accompanied by the activation of these kinases [75]. Interestingly, in the hypoxic goldfish heart, the molecular events of downstream NO generation exclude the involvement of the cGMP-dependent signalling [75]. Non-cGMP-dependent pathways represent an important route for NO to control its molecular targets.…”
Section: The Nos/no System In the Fish Heart Under Hypoxiamentioning
confidence: 91%
“…In the mammalian heart, under basal conditions and in the presence of low O 2 , the PI3-K/Akt pathway controls eNOS activity, and thus NO generation and the consequent NO-dependent signalling, being protective for the heart [76,77]. The same occurs in hypoxia-tolerant fish in which, as observed in the perfused goldfish heart, exposure to low O 2 is accompanied by the activation of these kinases [75]. Interestingly, in the hypoxic goldfish heart, the molecular events of downstream NO generation exclude the involvement of the cGMP-dependent signalling [75].…”
Section: The Nos/no System In the Fish Heart Under Hypoxiamentioning
confidence: 99%
See 2 more Smart Citations